ACUTE- AND DELAYED-ONSET ENDOPHTHALMITIS AFTER OPEN GLOBE INJURIES: Clinical Features and Visual Acuity Outcomes. Issue 4 (April 2023) - Hudson, Julia L.; Fan, Jason C.; Smiddy, William E.; Sridhar, Jayanth; Yannuzzi, Nicolas A.; Flynn, Harry W.
Abstract : The rate of endophthalmitis in the current study was low, and patients with open globe–related endophthalmitis generally have poor visual outcomes. The study highlights that despite use of intravitreal antibiotics at primary closure, delayed-onset endophthalmitis cases may develop in the setting of compromised Zone 1 wound integrity. Abstract : Purpose: The purpose of the study was to report the clinical features and best-corrected visual acuity outcomes in patients with acute- and delayed-onset endophthalmitis after open globe injuries. Methods: The study included a retrospective, comparative, consecutive case series of patients with endophthalmitis after open globe injury between January 2016 and October 2020 at the Bascom Palmer Eye Institute. Results: Acute-onset endophthalmitis accounted for 16 of 20 cases (80%), and all cases were diagnosed at the initial examination. Delayed-onset endophthalmitis cases, occurring more than 2 weeks after injury, accounted for 4 of 20 cases (20%) and were because of Zone 1 wound leaks and infections. Factors associated with endophthalmitis included presence of a retained intraocular foreign body (11/20 [55%]) and delay of presentation >24 hours (15/20 [75%]) ( P < 0.001 and 0.002, respectively). The mean presenting best-corrected visual acuity was logMAR 1.64 (20/800), and the mean best-corrected visual acuity at the last follow-up was logMAR 1.22 (20/300). Conclusion: In patients with open globe injury–related endophthalmitis, visual acuity outcomes are generally poor. Despite intravitreal antibiotics at primary closure, delayed-onset endophthalmitis cases may develop in the setting of compromised Zone 1 wound integrity.